Toledot Yeshu in context: the Jewish "Life of Jesus" in ancient, medieval, and modern history - Barbu, Daniel; Doiṭsh, Yaʿaḳov (Texts and studies in ancient Judaism, 2020)
Das jüdische »Leben Jesu« oder Toledot Yeshu bietet eine polemische Darstellung der Anfänge des Christentums. Der vorliegende Band betrachtet diese Erzählung als Gegenstand der Geschichte, hinterfragt ihre Überlieferung, Rezeption und Funktion innerhalb der verschiedenen historischen Schauplätze, in denen sie zirkulierte, und versucht, ihre Bedeutung sowohl für Juden als auch für Nichtjuden von der Antike bis zur Neuzeit zu verstehen.InhaltsübersichtDaniel Barbu/Yaacov Deutsch: Introduction: Reading Toledot Yeshu in Context – William Horbury: Titles and Origins of Toledot Yeshu – Daniel Stökl Ben Ezra: On Some Early Traditions in Toledot Yeshu and the Antiquity of the »Helena« Recension – Gavin McDowell: The Alternative Chronology: Dating the Events of the Wagenseil Version of Toledot Yeshu – Gideon Bohak: Jesus the Magician in the »Pilate« Recension of Toledot Yeshu – Sarit Kattan Gribetz: The Mothers in the Manuscripts: Gender, Motherhood, and Power in Toledot Yeshu – Alexandra Cuffel: Toledot Yeshu in the Context of Polemic and Sīra Literature in the Middle East from the Fatimid to the Mamluk Era – Jonatan M. Benarroch: »A Real Spark of Sama'el”: Kabbalistic Reading(s) of Toledot Yeshu – Daniel Barbu/Yann Dahhaoui: The Secret Booklet from Germany: Circulation and Transmission of Toledot Yeshu at the Borders of the Empire – Stephen Burnett: Martin Luther, Toledot Yeshu , and »the Rabbis« – Evi Michels: Yiddish Toledot Yeshu Manuscripts from the Netherlands – Claudia Rosenzweig: The »History of the Life of Jesus« in a Yiddish Manuscript from the Eighteenth Century (Ms. Jerusalem, NLI, Heb. 8° 5622) – Yonatan Moss: »I Am Not Writing an Apology”: Samuel Krauss's Das Leben Jesu in Context